Uji Kinerja Dry Cell Electrolyzer Dengan Pengaruh Konsentrasi Elektrolit Terhadap Produksi Hidrogen sebagai Sumber Energi Fuel Cell - Sheli Fitriyani; Erlinawati; Sahrul Effendy (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
Hydrogen is a renewable energy source with the potential to replace fossil fuels due to its eco-friendly nature. This study aims to conduct a performance test of dry cell electrolyzer with variations in KOH electrolyte concentration so that optimal hydrogen production in fuel cells can be determined. The dry cell was chosen to mitigate explosion risks in wet cells caused by short circuits and uncontrolled gas pressure in previous studies. KOH concentrations from 0.1 M to 0.5 M were tested at 10 V and 12 V for 30 minutes. The results indicate that a 0.3 M concentration at 12 V achieved the highest hydrogen yield of 1.1829 liters. The optimum condition was found at 0.3 M and 10 V with 37% efficiency, producing 0.8206 liters of hydrogen with an SEC of 31,656.65 J/L. This hydrogen powered a PEM fuel cell, achieving a maximum efficiency of 45.2% under an LED lamp load. This modification highlights potential improvements in electrolyzer performance for clean energy applications.